2018
DOI: 10.1016/j.bbi.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress in mice is a suitable model for Irritable Bowel Syndrome but does not predispose to colitis nor increase susceptibility to enteric infections

Abstract: Neonatal period is characterized by an immature intestinal barrier. Scattered evidence suggests that early life stressful events induce long lasting alterations of intestinal homeostasis mimicking Irritable Bowel Syndrome (IBS). Those observations highlighting defect of intestinal barrier by early life stress questioned its potential role as a risk factor for gastrointestinal disorders such as colitis and infections. In this study, we aimed to analyze if maternal separation (MS) in mice mimicks IBS main featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…In the absence of later-life stress, RMS does not have significant effects on TNF-α expression in a range of regions and tissues, including hippocampus (Banqueri et al, 2019;Zhu et al, 2017), dorsal striatum (Banqueri et al, 2019), PFC (Banqueri et al, 2019), lung (Avitsur et al, 2006), colon (Lennon et al, 2013;Pierce et al, 2014), genitourinary tract (Pierce et al, 2014), splenocytes (Kiank et al, 2009), or plasma (Barouei et al, 2015;Grassi-Oliveira et al, 2016). However, Riba et al (2017Riba et al ( , 2018 reported elevated levels of TNF-α in the small intestine of RMS animals sacrificed at PND 50. The reasons for this discrepancy are unclear but may include use of pair housing and sacrifice closer to the conclusion of RMS than most other included studies of long-term effects.…”
Section: Long-term Effects Of Rms In the Absence Of Later-life Stressmentioning
confidence: 99%
“…In the absence of later-life stress, RMS does not have significant effects on TNF-α expression in a range of regions and tissues, including hippocampus (Banqueri et al, 2019;Zhu et al, 2017), dorsal striatum (Banqueri et al, 2019), PFC (Banqueri et al, 2019), lung (Avitsur et al, 2006), colon (Lennon et al, 2013;Pierce et al, 2014), genitourinary tract (Pierce et al, 2014), splenocytes (Kiank et al, 2009), or plasma (Barouei et al, 2015;Grassi-Oliveira et al, 2016). However, Riba et al (2017Riba et al ( , 2018 reported elevated levels of TNF-α in the small intestine of RMS animals sacrificed at PND 50. The reasons for this discrepancy are unclear but may include use of pair housing and sacrifice closer to the conclusion of RMS than most other included studies of long-term effects.…”
Section: Long-term Effects Of Rms In the Absence Of Later-life Stressmentioning
confidence: 99%
“…MS has been associated with alterations in the differentiation and distribution of enteroendocrine cells in the gut epithelium (301) and a defect in Paneth cells (276,284) . Notably, the numbers of enterochromaffin cells in the colon are increased in MS animals compared with controls (264,265,275) .…”
Section: The Maternal Separation Modelmentioning
confidence: 99%
“…Moreover, MS rats show more colonic damage after dextran sulphate sodium or 2,4,6-trinitrobenzenesulphonic acid-induced colitis than non-stressed animals and as a result, they also lose more weight, indicating that they are more sensitive to experimental colitis (305307) . There is mounting evidence that MS produces long-term gut paracellular and transcellular hyper-permeability to ions and macromolecules (81,262,272,276,299,302,306,308311) . Remarkably, stress-induced intestinal hyperpermeability appears to be glucocorticoid-dependent, as it is evoked by the synthetic glucocorticoid dexamethasone and prevented by administration of a GR antagonist, similarly to an inhibitor of the myosin light chain kinase controlling epithelial cytoskeleton contraction (221) .…”
Section: The Maternal Separation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…MatSep rodents also develop autoimmune diseases. In a study examining parameters of irritable bowel syndrome, MatSep in mice induced proinflammatory status of T cells as indicated by activated splenic T cells and increased IFN‐γ secretion from splenic T cells after antiCD3/CD28 stimulation (Riba et al, ). Alterations in immune cell populations and functions have also been observed in various rodent strains exposed to MatSep including Sprague–Dawley, Wistar, and FSL rat strains as well as C3H/H3N and NMRI mouse strains (Carboni et al, ; Pinheiro et al, ; Riba et al, ; S. Roque, Mesquita, Palha, Sousa, & Correia‐Neves, ).…”
Section: Proinflammatory Mediators and Vasoactive Factors As Mechanismentioning
confidence: 99%